UNDERSTANDING THE TYPES OF BANK LOANS FOR MICROENTREPRENEURS - Barcelos, Priscilla Godoy Lobato (Revista Sistemática, 2022)
Access to finance is a fundamental challenge for microentrepreneurs, whose businesses often operate with limited capital and face cash flow volatility. This article explores the primary types of bank loans available to microentrepreneurs, including short-term loans, long-term loans, and lines of credit. Each financing option serves distinct purposes, addressing immediate working capital needs, capital investments, or flexible liquidity management. The paper discusses the characteristics, eligibility requirements, benefits, and challenges associated with these loan types. Furthermore, it highlights the persistent barriers microentrepreneurs encounter in accessing formal credit, such as limited financial literacy and collateral constraints. By fostering greater understanding and transparency of loan products and promoting financial education, microentrepreneurs can make more informed borrowing decisions that enhance their business sustainability and growth prospects. The article also underscores the role of inclusive banking policies and innovative financial technologies in expanding credit access for this vital economic sector.